The Balanced Scorecard / Translating Strategy Into Action - Kaplan Robert S; Norton David P (Harvard Business School Press, 1996)
An innovative management perspective that can be used to translate strategy for growth into operational terms. Preface, Measurement and Management in the Information Age, Why Does Business Need a Balanced Scorecard?, Measuring Business Strategy, Financial Perspective, Customer Perspective, Internal-Business-Process Perspective, Learning and Growth Perspective, Linking Balanced Scorecard Measures to Your Strategy, Structure and Strategy, Managing Business Strategy, Achieving Strategic Alignment: From Top to Bottom, Targets and Resource Allocation and Initiatives and Budgets, Feedback and the Strategic Learning Process, Implementing a Balanced Scorecard Management Program, Appendix: Building a Balanced Scorecard, Index.